Asthma in children born after infertility treatment: findings from the UK Millennium Cohort Study - Carson, C. (Oxford University Press, 2013)
STUDY QUESTION: Is asthma more common in children born after subfertility and assisted reproduction technologies (ART)? SUMMARY ANSWER: Yes. Asthma, wheezing in the last year and anti-asthmatic medication were all more common in children born after a prolonged time to conception (TTC). This was driven specifically by an increase in children born after ART. WHAT IS KNOWN ALREADY: Few studies have investigated any association between ART and asthma in subsequent children, and findings to date have been mixed. A large registry-based study found an increase in asthma medication in ART children but suggests underlying infertility is the putative risk factor. Little is known about asthma in children after unplanned or mistimed conceptions. STUDY DESIGN, SIZE, DURATION: The Millennium Cohort Study is a UK-wide, prospective study of 18 818 children recruited at 9 months of age. Follow-up is ongoing. This study analyses data from follow-up surveys at 5 and 7 years of age (response rates of 79 and 70%, respectively). PARTICIPANTS/MATERIALS, SETTING, METHODS: Singleton children whose natural mothers provided follow-up data were included. Mothers reported whether their pregnancy was planned; planners provided TTC and details of any ART. The population was divided into ‘unplanned’ (unplanned and unhappy), ‘mistimed’ (unplanned but happy), ‘planned’ (planned, TTC < 12 months), ‘untreated subfertile’ (planned, TTC >12 months), ‘ovulation induced’ (received clomiphene citrate) and ‘ART’ (IVF or ICSI). The primary analysis used the planned children as the comparison group; secondary analysis compared the treatment groups to the children born to untreated subfertile parents. Outcomes were parent report of asthma and wheezing at 5 and 7 years, derived from validated questions in the International Study of Asthma and Allergies in Childhood, plus use of anti-asthmatic medications. A total of 13 041 (72%) children with full data on asthma and confounders were included at 5 years of age, and 11 585 (64%) at 7 years. MAIN RESULTS AND THE ROLE OF CHANCE: Compared with planned children, those born to subfertile parents were significantly more likely to experience asthma, wheezing and to be taking anti-asthmatics at 5 years of age [adjusted odds ratio (OR): 1.39 (95% confidence interval (CI): 1.07, 1.80), OR: 1.27 (1.00, 1.63) and OR: 1.90 (1.32,2.74), respectively]. This association was mainly related to an increase among children born after ART (adjusted OR: 2.65 (1.48, 4.76), OR: 1.97, (1.10, 3.53) and OR: 4.67 (2.20, 9.94) for asthma, wheezing and taking anti-asthmatics, respectively). The association was also present, though reduced, at the age of 7 years. LIMITATIONS, REASONS FOR CAUTION: The number of singletons born after ART was relatively small (n = 104), and as such the findings should be interpreted with caution. However, data on a wide range of possible confounding and mediating factors were available and analysed. The data were weighted for non-response to minimize selection bias. WIDER IMPLICATIONS OF THE FINDINGS: The findings add to the growing body of evidence suggesting an association between subfertility, ART and asthma in children. Further work is needed to establish causality and elucidate the underlying mechanism. These findings are generalizable to singletons only, and further work on multiples is needed. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by a Medical Research Council project grant. No competing interests.